2017
DOI: 10.1177/0305735617705720
|View full text |Cite
|
Sign up to set email alerts
|

Maternal engagement with music up to nine months post-birth: Findings from a cross-sectional study in England

Abstract: There is significant evidence of the benefits of music for babies and emerging evidence that music may also benefit mothers' wellbeing. However, there is a lack of current large-scale data documenting maternal engagement with music in England. This cross-sectional survey study used descriptive and inferential statistics to examine how 473 mothers living in England engaged with music between 1-9 months post-birth, and regression models to examine demographic and musical predictors of this engagement. Findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Regarding other musical behaviours, we had 3 specific measures: how often women listened to music (rarely, a couple of times a week, daily <1hr, daily 1–2hrs, daily 3–5hrs, daily 5+hrs), whether they had attended a concert in the past month, and how much their partner (if applicable) sang to the infant (4-point scale: not at all, a bit, quite a lot, very much ). These measures on wider musical behaviours were based on the questions asked as part of the previous study on musical engagement in mothers with young infants involving a separate sample of women (Fancourt & Perkins, 2017a). However, we chose to omit questions on how often mothers made music (such as playing an instrument) due to the very low levels of such engagement reported in the previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding other musical behaviours, we had 3 specific measures: how often women listened to music (rarely, a couple of times a week, daily <1hr, daily 1–2hrs, daily 3–5hrs, daily 5+hrs), whether they had attended a concert in the past month, and how much their partner (if applicable) sang to the infant (4-point scale: not at all, a bit, quite a lot, very much ). These measures on wider musical behaviours were based on the questions asked as part of the previous study on musical engagement in mothers with young infants involving a separate sample of women (Fancourt & Perkins, 2017a). However, we chose to omit questions on how often mothers made music (such as playing an instrument) due to the very low levels of such engagement reported in the previous study.…”
Section: Methodsmentioning
confidence: 99%
“…In order to provide some more empirical data, this article focuses on a specific population: mothers with young infants. Previous research has provided insight into the musical activities that mothers engage with; for example, a recent study showed that 59% of mothers in the first 9 months post-birth sing to their babies on a daily basis, and 71% listen to music on a daily basis, but only 22% of mothers attend regular music classes with their babies (Fancourt & Perkins, 2017a). This research has also suggested specific musical predictors of musical behaviours in mothers.…”
mentioning
confidence: 99%
“…9 These ritualized performances become an important part of caregiver-infant interactions. According to parental report, routine singing to infants increases parents' well-being, self-esteem, and reciprocal parent-infant bonding, 10 while also soothing infants and reducing their distress. 11 Infants' responses to these musical interactions are shaped by their cumulative exposure to music and by concurrent auditory, motor, and cognitive development.…”
Section: Music Perception In Infancy -Rhythm and Melodymentioning
confidence: 99%
“…As the first music teachers in infants’ lives, researchers have emphasized the crucial roles caregivers play in infants’ music development (Fancourt & Perkins, 2018; Valerio et al, 2011; Valerio, Reynolds, Morgan, & McNair, 2012). According to Trehub (2003), singing to infants may affect infant arousal (e.g., sleeping, wakefulness, movements, and crying), may affect infant-caregiver bonding, and may increase infant survival rates.…”
Section: Music-making With Caregiversmentioning
confidence: 99%